1965
DOI: 10.3181/00379727-118-29964
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Caries Induced in Animals by Streptococci of Human Origin.

Abstract: Traditionally, lactobacilli have been considered the principal cause of caries, but recent findings have questioned this concept. Orland ( 1 ) succeeded in producing experimental caries by infecting gnotobiotic rats with a strain of streptococcus. More recently, Fitzgerald et a1 ( 2 ) confirmed these findings, and Fitzgerald and Keyes (3) established the cariogenicity of another strain of streptococcus in hamsters. These 2 strains of streptococci were shown to be host-specific with regard to cariogenicity: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0
1

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(68 citation statements)
references
References 0 publications
1
66
0
1
Order By: Relevance
“…Streptococcus mutans is cariogenic in experimental animals (7,8,17) and is believed to be important in the initiation of smooth surface dental caries in humans (5,6,14). Bacteriocins produced by S. mutans are therefore of considerable interest since, by inhibiting other organisms, they may play important roles in establishing and/maintaining this pathogenic species in the oral cavity.…”
mentioning
confidence: 99%
“…Streptococcus mutans is cariogenic in experimental animals (7,8,17) and is believed to be important in the initiation of smooth surface dental caries in humans (5,6,14). Bacteriocins produced by S. mutans are therefore of considerable interest since, by inhibiting other organisms, they may play important roles in establishing and/maintaining this pathogenic species in the oral cavity.…”
mentioning
confidence: 99%
“…We have reported that the culture filtrate of Streptomyces globisporus 1829, a strain isolated from soil, is capable of rapidly lysing cells of cariogenic steptococci isolated from carious lesions in both rodents and humans (24,25). Streptococcus mutans, a type of cariogenic bacteria, has been shown to form dental plaques composed of extracellular polysaccharides of a dextran type and to induce dental caries when inoculated into the oral cavities of experimental animals maintained on a high sucrose diet (5,16,27). Fitzgerald (4) found that in some hamsters receiving dextranase in their drinking water significantly less plaque formation occurred, and fewer dental caries developed than in animals not receiving the enzyme; an attempt has been made to control dental caries by applying dextranase (15,18,21).…”
mentioning
confidence: 99%
“…Immunofluorescence techniques to identify bacteria in carious dentin have been used in two main different ways: (1) by taking carious dentin samples with a spoon excavator, transferring the sample to a microscope slide and labeling the sample with fluorescent antibodies [Bibby and Hine, 1938;Zinner et al, 1965] and (2) by obtaining very thin sections from extracted carious teeth and labeling the section with fluorescent antibodies [Sumitani et al, 1972;Pekovic et al, 1987]. Kermans et al [1981] used immunolabeling and transmission electron microscopy for the identification of specific microorganisms in thin sections of carious dentin.…”
Section: Discussionmentioning
confidence: 99%